Discrimination of ascitic fluid infection in malignant ascites by polymorphonuclear neutrophil ratio and count: Investigating the validity of count ≥250/mm3 as the one‐size‐fits‐all criterion. Issue 2 (6th August 2020) - Moon, Hae; Kim, Hak Jin; Woo, Sang Myung; Park, In Hae; Sim, Sung Hoon
Abstract: Aim: Neutrocytic ascites, traditionally defined as a polymorphonuclear neutrophil count ≥250/mm 3, is infrequently reported during paracenteses to relieve malignant ascites (MA). This study aims to explore new potential diagnostic criteria to discriminate ascitic fluid infection associated with MA and to examine the clinical and laboratory characteristics of neutrocytic ascites. Methods: The investigators retrospectively collected data on paracenteses to relieve MA at the Emergency Department of National Cancer Center, Korea, from January 2014 to February 2017. We analyzed the patients whose ascites fulfilled the traditional criteria for classification as neutrocytic ascites; polymorphonuclear neutrophils ≥250/mm 3 with no history of either hepatocellular carcinoma or liver cirrhosis. Results: In total, 1467 patients underwent paracentesis to relieve MA. Excluding 98 follow‐up paracenteses cases, 112 cases (8.2%) showed neutrocytic ascites. Of these 112 patients, 27 (24.1%) had positive culture results. Receiver‐operating characteristic analysis indicated that the area under the curve (AUC) values were 0.90 (95% CI 0.82‐0.95) and 0.86 (95% CI 0.78‐0.92) for polymorphonuclear neutrophil ratio and count, respectively. The difference between the two AUCs was not statistically significant ( P = .29). Moreover, the best cutoff points were 70% and 1500/mm 3 for polymorphonuclear neutrophil ratio and count, respectively. In addition, extensive liver metastasis was a significant independent risk factor of MA associated with ascitic fluid infection. Conclusions: Both polymorphonuclear neutrophil ratio and count had good discriminative abilities for culture results in MA. Polymorphonuclear neutrophil ratio was somewhat better despite lacking statistical significance compared to polymorphonuclear neutrophil count, with 70% as best cutoff.